PENGARUH SUHU TEMPER PADA PROSES AUSTEMPERING TERHADAP STRUKTUR MIKRO DAN SIFAT MEKANIS BAJA BAINITIK NIR KARBIDA (CARBIDE-FREE BAINITIC STEEL) UNTUK BAJA TAHAN PELURU - , AJI DANANJAYA, Dr. Kusmono, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Armour steel is steel that widely used as a material for armoured vehicles. The requirements for armour steel are high values in strength, hardness, toughness and good ballistic performance. The aim of this research is to study the effects of austempering process to physical, mechanical, and ballistic properties of CFB steels (carbide-free bainitic steels) for armour steel application. Three different CFB steels with compositions of C (0.3%), Si (0.75-1%), Cr (1.7-2.3%), Mn (2-2.21%), Mo (0.25%), Cu (0.28-0.48%) and Ni (0.3-2.4%) were made by sand casting. The austempering process were first prepared by heating CFB steels in a furnace until temperature of 900Â°C for 20 minutes. Furthermore, steels were quenched in a salt-bath (80% and 20% ) at temperature of 300 and 400Â°C for 20 minutes then cooled in air. Microstructure observation, tensile, impact, hardness, and ballistic tests were conducted in this study. Results showed that austempering process at 300Â°C on CFB steel 0.3% Ni increased tensile strength by 112.4% (from 505.25 to 1073.25 MPa) and hardness by 3.8% (from 434.5 to 450.1 kg/mmÂ²) and also impact toughness by 17.4% (from 15.3 to 18 J). Ballistic test result showed that all CFB steels didnât pierced by projectile. It means that CFB steels have a good potential for armour steel.